Network security : (Morgan Kaufmann/Elsevier, 2008)
Network Security: Know It All explains the basics, describes the protocols, and discusses advanced topics, by the best and brightest experts in the field of network security. Assembled from the works of leading researchers and practitioners, this best-of-the-best collection of chapters on network security and survivability is a valuable and handy resource. It consolidates content from the field's leading experts while creating a one-stop-shopping opportunity for readers to access the information only otherwise available from disparate sources.